Reconfiguration et permanence des acteurs de la gestion des infrastructures urbaines à l’aune du fait numérique - Victor Bayard (Netcom)
The interactions between the stakeholders involved in technical infrastructure management are partly determined by prevailing tendencies. These tendencies are linked to historical and territorial factors that have accompanied the creation and evolution of these stakeholders. In this article, we will attempt to understand how these tendencies are affected by the digital economy and smart city stakeholders. We will draw on a field study (the Data City experiment), a set of qualitative interviews and a literature review focusing on the management of Parisian technical networks and other field studies related to the smart city to analyse the trajectories of network management in the territory. The aim here is to understand the link between the tendencies in stakeholder relations and the influence of smart city representations and technologies, particularly in relation to urban data. We will show that the major tendencies in network management are leading (in our field) to a partial reconfiguration of stakeholders, and above all to the integration of those related to the digital economy.